Obstacles To Teaching and Learning Arabic In Middle Schools in Rania District: Eleventh Grade Model - Mohammed Hamad Amin Rasul (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The failure in the process of teaching and learning the Arabic language in our middle schools is something no one can deny, and that it needs to conduct many studies in search of these obstacles that hindered the process of teaching and learning Arabic in the district of Rania. You will hinder her. We present these hindrances to the scientific view concerned with teaching and learning. We identify and classify these obstacles. And we present the results of the questionnaires that we conducted in schools through scientific experimental tables.We intend in this research to find scientific solutions to these obstacles as a recommendation to the Ministry of Education in Kurdistan Region. I hope that the content of this research will be used to overcome the obstacles to teaching and learning the Arabic language, and to encourage teachers to reform their teaching method for the better. In this regard, we see that the process of teaching and learning the Arabic language is an applied and communicative process that is completely different from purely scientific subjects, such as mathematics.